Foramen Magnum Meningioma – A common histological tumor in a rare location (Balneo and PRM Research Journal, 2021)
Meningiomas located in the foramen magnum area are uncommon. We report the case of a patient with a mass lesion compressing the medulla, who was admitted to the Neurology Department for cervical pain and  tetraparesis. On the MRI (Magnetic Resonance Imaging) examination, specific features for a meningioma were described, confirmed later by the histopathological examination. The patient presented a favorable evolution, at only one month after surgery.
Keywords: Meningioma; Tetraparesis; Foramen Magnum; Neurosurgery